2013
DOI: 10.1007/s00216-013-7427-7
|View full text |Cite
|
Sign up to set email alerts
|

NIR Raman spectra of whole human blood: effects of laser-induced and in vitro hemoglobin denaturation

Abstract: Care must be exercised in the use of Raman spectroscopy for the identification of blood in forensic applications. The 785 nm excited Raman spectra of dried whole human blood are shown to be exclusively due to oxyhemoglobin (oxyHb) or related hemoglobin denaturation products. Raman spectra of whole blood are reported as a function of incident 785 nm laser power and features attributable to heme aggregates are observed for fluences on the order of 104 W/cm2 and 20 sec signal collection times. In particular, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
83
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(90 citation statements)
references
References 26 publications
(70 reference statements)
7
83
0
Order By: Relevance
“…The bands associated with these laser-induced effects in whole blood agreed with similar aggregation/ denaturation bands assigned by previous research groups in samples of isolated RBCs. 201 As mentioned above, the detection and monitoring of glucose in blood has been a prime target for many scientists because of its importance to diabetes medicine. One of the pioneers in the Raman detection of glucose in whole blood was MIT's Michael Feld.…”
Section: Whole Bloodmentioning
confidence: 99%
See 1 more Smart Citation
“…The bands associated with these laser-induced effects in whole blood agreed with similar aggregation/ denaturation bands assigned by previous research groups in samples of isolated RBCs. 201 As mentioned above, the detection and monitoring of glucose in blood has been a prime target for many scientists because of its importance to diabetes medicine. One of the pioneers in the Raman detection of glucose in whole blood was MIT's Michael Feld.…”
Section: Whole Bloodmentioning
confidence: 99%
“…210 The assignment of certain bands to fibrin was later revised 211 as more was learned about the effect of intense laser exposure. 201 After understanding of the chemical heterogeneity of blood spatters increased, Lednev et al proposed that multi-dimensional Raman measurements be attempted, 212 and in 2012 they used the technique to discriminate between dry samples that contained mixtures of human blood and semen. With their multivariate algorithm, mixtures with blood content higher than 80% could not be distinguished from pure blood, while 5% blood in a mixture resulted in a Raman spectrum distinguishable from the spectrum of pure semen 213 (later studies would report on the successful discrimination between dry samples of peripheral blood and menstrual blood, 214 and also between races 215 ).…”
Section: Whole Bloodmentioning
confidence: 99%
“…Raman spectroscopy has been recognized as a potentially useful method in physics, chemistry and biology fields for investigations of vibrational modes. In the past few years, the use of Raman spectroscopy to identify human body fluids, important components in many crime scene investigations, has been proposed and demonstrated [3]. Lowering costs, minimal sample and almost no reagent are needed for Raman spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Raman spectroscopy yields scattering peaks characteristic for blood by exciting the sample at a wavelength of 752 nm or 785 nm . These peaks correspond to: (i) (Oxy)Haemoglobin (1000, 1368, 1542 and 1620 cm −1 ) and probably fibrin (967, 1248, 1342 and 1575 cm −1 ) for excitation at 752 nm.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that OxyHaemoglobin and Haemoglobin denaturation products (419, 570, 677, 754, 1128, 1311, 1374, 1398, 1549, 1582, 1638 cm −1 ) are also detected at 785 nm excitation and at low laser power (1.9 mW). These peaks are however subjected to shifts as a function of higher laser power and age before and after drying . HSI records the reflectance spectrum of a sample in the visible light region, where blood exhibits characteristic absorption band: a strong, narrow absorption band centred at 415 nm (Soret band) and two weaker, broader bands between 500 and 600 nm (β and α bands) .…”
Section: Introductionmentioning
confidence: 99%